Evaluasi Kandungan Fitokimia, Kapasitas Antioksidan, dan Toksisitas Ekstrak Daun Stevia rebaudiana - Frankson, Desvin; Hendrawan, Siufui; Ferdinal, Frans (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Oxidative stress leads to numerous clinical problems, such as autoimmune, vascular and respiratory impairment, as well as many other degenerative diseases. While daily exposure to UV light, air pollution, and smoke largely contribute to oxidative stress, endogenous antioxidants mostly fail to neutralize these high amounts of free radicals. Stevia rebaudiana or â€œcandyleafâ€ is largely found in Indonesia, known for its application as a natural sweetener, owing to its content of stevioside compound. This study is experimental research which aims to assess the potential of stevia extract as an antioxidant supplement, which has not been widely applied. In vitro study was performed by extracting stevia leaves in methanol through simple maceration and percolation methods. Subsequently, the stevia extract was subjected to biochemical analysis, i.e. phytochemical screening, total phenolic content assay, antioxidant capacity assay, and toxicity assay. Herein, we found that stevia extract contains flavonoid, saponin, tannin, terpenoid, and phenolic compounds, with total phenolic content of 86.30Â±1.14 mg GAE/g DW. Moreover, antioxidant capacity assay through 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) method showed that IC50 of stevia extract is 20.13 Âµg/mL, slightly higher than Trolox (vitamin E analog) with IC50 of 16.50 Âµg/mL, which indicated that stevia extract is a very strong antioxidant. As for toxicity bioassay, Brine Shrimp Lethality Test indicated that stevia extract is non-toxic with LC50 value of 3388.44 Âµg/mL.